The Effect of Diversification and Business Risk on Financial Performance of Manufacturing Companies in the Various Industries Sector on the Indonesia Stock Exchange in 2019-2022 - Nisrina Khairani Solinah; Zuhrotul Isnaini (Cita konsultindo, 2024)
This study aims to analyze the impact of diversification and business risk on the financial performance of various industrial sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2022 period using the Path Analysis model. The variables studied were the Herfindahl Index, Return On Assets, and Business Risk. The main data of this research comes from secondary data. The sampling method used purposive sampling method. The results state that diversification affects financial performance, business risk affects financial performance, diversification does not affect business risk, and business risk does not serve as a mediator in the relationship between diversification and financial performance.